Compilation of components of urban architectural spaces durability emphasizing the of everyday life rhythms (Case study: Tabriz Bazaar) - Elham Hatami Golzari; Ahmad Mirza kouchak khoshnevis; Qader Bayzidi; Foad Habibi (تحقیقات کاربردی علوم جغرافیایی)
Persistent spaces and phenomena over time and load and become part of collective memories. In this way, paying attention to the durability of space design increases the sense of belonging to space, in this case space does not belong only to the present. Considering the importance of sustainability, the purpose of this study is to identify the factors affecting the survival of urban spaces, with emphasis on the multiplication of effective daily life in three areas of the Tabriz market (Grand mosque, Rasteh bazar, and Saheb-ol-amr square). The research method is a descriptive-analytic study used for collecting information using documentary and field (survey) method. Also, in this research, in addition to applying the qualitative method for analyzing the causes of durability in the studied areas, quantitative method of analysis of variance was used to investigate the durability of urban spaces in the studied areas. The findings of the research indicate that within the boundaries of the Grand mosque, the spirituality factor (0.376), socioeconomic and functional (0.352), in the range of Rasteh bazar of the identity factor (0.314) and within the range of Saheb-ol-amr square, the factor of spirituality (0.327) and identity (0.305) is the most important reason for the survival of the studied areas. The results also show that the various components of everyday life have oddities that, while repeated in the daily life cycle, are linear (progressive, regressive, and fixed), which in two parts are all in part and in part In general, they affect the survival and decline of spaces. In the meantime, the approaches and cultural components derived from the whole are in part like the rituals and cultures of a community, have and will have a significant impact on the survival and increase of durability of spaces. Therefore, the continuation of rituals and cultural ceremonies in the studied areas can provide a lasting space for these spaces.